Coconut varieties tolerant to root (wilt) disease - Thomas, Regi J; Shareefa, M; Krishnakumar, V; Chowdappa, P (Indian Horticulture, 2019)
The coconut root (wilt) disease, reported over a century ago in Kerala, is now prevalent in eight southern districts. Occurrence of this disease has also been reported from the remaining six districts of Kerala and also from some parts of Tamil Nadu, Karnataka and Goa adjoining to Kerala. A survey conducted during 1996 revealed that 24.1% of the 102 million palms in the disease endemic region are root (wilt) affected. The disease is caused by phytoplasma and transmitted by lace wing bug (Stephanitis typica) and plant hopper (Proutista moesta). As the disease cannot be controlled by any conventional plant-protection measures, developing resistant varieties and other management strategies are the most practical methods for the management of this malady.